Pengaruh virus corona (covid-19) terhadap ruas kinerja jalan disekitar pabrik GSI sukalarang - Mirdianti, Asti; Paikun (Jurnal TESLINK : Teknik Sipil dan Lingkungan, 2021)
Since the factories began operating, they had an impact in the form of congestion that occurred on Jalan Sukabumi-Cianjur, precisely in front of the P.T. Glostar Indonesia (GSI) at the position of Km.13 until the new road access to PT. Pratama Abadi Industri. However, currently the world is in an uproar with a virus called Corona Virus or Covid-19 which has occurred in the last few months in Indonesia in 2020. Of course this will have an impact on all aspects including the level of road service, so a comparative study of road performance is made. around the GSI Sukalarang factory from Hatun 2017 to 2020. From the survey and calculation results, it can be concluded that the performance of roads with service levels in the current GSI factory area (2020) compared to the previous year (2017) at the same location has decreased which is indicated by reduced vehicle volume, vehicle speed. decreased, reduced vehicle density, and good service levels. From the data obtained, the Covid-19 Pandemic has an effect on traffic volume and road performance, resulting in a decrease in vehicle volume in 2020. In 2017 the traffic volume on Saturdays was 21684 vehicles and 8407.8 SMP / hour, for 2020 on Saturdays, namely 10471 vehicles and 5500.6 SMP / hour decreased by 48.3%. While in 2017 the traffic volume on Monday was 26430 vehicles and 9467.35 SMP / hour, for 2020 Monday, namely 23740 vehicles and 9623.85 SMP / hour decreased by 89.9%.